2001
DOI: 10.1128/jvi.75.18.8424-8433.2001
|View full text |Cite
|
Sign up to set email alerts
|

Feline Leukemia Virus DNA Vaccine Efficacy Is Enhanced by Coadministration with Interleukin-12 (IL-12) and IL-18 Expression Vectors

Abstract: The expectation that cell-mediated immunity is important in the control of feline leukemia virus (FeLV

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 74 publications
1
47
0
2
Order By: Relevance
“…The majority of recent data describes adjuvant effects that modulate or potentialize the Th1 immune response pattern (11,21,24,25,37). In most of these studies cytokines or plasmids encoding cytokine genes to amplify this kind of immune response are used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of recent data describes adjuvant effects that modulate or potentialize the Th1 immune response pattern (11,21,24,25,37). In most of these studies cytokines or plasmids encoding cytokine genes to amplify this kind of immune response are used.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrated that co-administration of plasmids encoding cytokine genes as adjuvants significantly enhanced immune response. In another study the co-administration of feline leukemia virus DNA vaccine with IL-12 and IL-18 expression vectors improved vaccine efficacy (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, IL-18 was reported to play a major role in resistance against Yersinia, mycobacterial, cryptococcal, Salmonella, Leishmania, herpes simplex virus type 1, feline leukemia virus, and vaccinia virus infections (51)(52)(53)(54)(55)(56)(57)(58). Similar to H. pylori, these infectious agents elicit Th1-dominated immune responses (51,52,55,57,59). Given that IL-18 primarily is involved in protection as a coregulator of Th1 development together with IL-12, it is not surprising that we found a strong dependence on IL-18 for the development of host resistance also against H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…O objetivo principal era estabelecer um modelo animal para as pesquisas com outros retrovírus, em destaque, o Vírus da imunodeficiência humana (HIV) (HANLON et al, 2001). Diversas vacinas em diferentes formatos foram desenvolvidas, mas comparar os resultados de eficácia sempre foi motivo de discussão, principalmente, pelo emprego de diferentes vias de inoculação, cepas virais e amostragens (SPARKES, 1997;LUTZ et al, 2009 (LUTZ et al, 2009), nenhuma vacina promove 100% de proteção e não previne a infecção, no entanto, a vacinação previne o desenvolvimento de antigenemia persistente.…”
Section: Vacinaçãounclassified